Pemanfaatan Tandan Kosong Sawit (TKS) untuk Pembuatan Pulp dan Pengolahan Limbah Cairnya - Yusup Setiawan; Sri Purwati; Kristaufan Joko Pramono (Center for Pulp and Paper, 2005)
Palm oil empty fruit bunches is one of solid waste discharges from crude palm oil industry that the amount is very abundant and it is not utilized optimally yet to be a product having added value. Investigation on the palm oil empty fruit bunches utilization to be a bleached pulp cooked by soda process and soda-anthraquinone processes have been carried out. Palm oil empty fruit bunches cooked by both soda process and soda-anthraquinone process were done by cooking chemicals varied on the concentration of 10% - 16% in the ratio of 4.0 at the temperature of 160oC for 3.5 hrs. Unbleached pulp produced was bleached with the ODEoDD bleaching sequences. Kappa number, yield and the other parameters were analyzed. Kappa number, yield and the other parameter of this bleached pulp were tested. Wastewater discharges from soda cooking process using cooking chemicals of 16% was collected and characterized for parameters such as COD, BOD5, TSS, and pH. This wastewater was treated by anaerobic-aerobic-chemicals treatment processes. Hydraulic Residence Time (HRT) on the anaerobic treatment and the aerobic treatment was varied of 1 to 5 days and 1 to 3 days, respectively. Alum and polyelectrolyte (PE) were used as coagulant and flocculants in chemicals treatment process. Result revealed that the optimum cooking condition of palm oil empty fruit bunches for both soda process and soda- anthraquinone process use cooking chemicals of 16%. The pulp produced by soda process and soda-anthraquinone process have yield of 30.65% and 37.39%, kappa number of 28.89 and 16.69, and alpha-cellulose of 76.62% and 76.77%, respectively. Wastewater discharges per batch cooking process which is mainly from pulp washing process is around 20 liters or 150 m3 per ton pulp. Wastewater discharges from soda cooking process using cooking chemicals of 16% containing COD of 9,680 mg/l, BOD5 of 5,135 mg/l, and TSS of 6,220 mg/L. This wastewater was treated by anaerobic-aerobic-chemical treatment processes which could reduce COD up to 97.18%, BOD5 up to 99.24% and TSS up to 99.74%. The quality of treated wastewater was under effluent standard for pulp and paper industry.